The study of the incidence of neural tube defects in hospitals of Kurdistan province in 1990 - Leyla Hasheminasab; Farzaneh Zaheri; Ronak Shahoe; Fariba Raanaei (Kurdistan University of Medical Sciences, 2017)
Introduction & Aim: Neural tube defects are among the common abnormalities of the central nervous system in neonates, which are often fatal and a global social medical problem. The aim of this study was to determine the incidence of neural tube defects in hospitals of Kurdistan province in the West of Iran. Materials and Methods: This prospective and descriptive study was conducted in all governmental hospitals of the province in the year 2011. All cases of neural tube defects that were born during the study were reviewed. Demographic, medical and obstetric information of the units was collected by a researcher-made questionnaire. Results: In one year, 27153 cases of birth occurred in the province, of which 46 had neural tube defects. The incidence of defects was 1.68 in 1,000 births. The majority of mothers (60.9%) were between the ages of 25 and 16 years, with no history of the current disease (89.1%) and abortion (88%). The distribution of various defects was described. Conclusion: According to the results of the study, the incidence of neural tube defects in Kurdistan province is less than previous studies in other regions of Iran. This decline seems to be due to improvements in prenatal care and social awareness raising and mothers awareness raising over the last decade.